2004
DOI: 10.1021/ja045385q
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipid Chain Lengths in α-Galactosylceramides on Cytokine Release by Natural Killer T Cells

Abstract: Glycolipid presentation by CD1 proteins has emerged as an important aspect of antigen recognition, and presentation of alpha-glycosylceramides by CD1d to natural killer T cells has become a central focus in understanding how glycolipid presentation can influence immune responses. An alpha-galactosylceramide containing relatively long lipid chains has been the subject of intense study because, when presented by CD1d to natural killer T cells, it stimulates the release of both proinflammatory and immunomodulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
166
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(171 citation statements)
references
References 19 publications
5
166
0
Order By: Relevance
“…Previously, we showed that absence of the 4-OH alone had a relatively small influence on antigenic potency and a Ͻ5-fold effect on equilibrium binding of a soluble TCR or binding of CD1d tetramers loaded with this variant glycolipid to live cells (28). The shorter C 8 acyl chain of PBS-25 and a C 14 analog of ␣-GalCer also did not cause a great decrease in antigenic potency (29,30). Based on these findings, we conclude that the combined differences of the shortened acyl chain and the absence of the sphingosine 4-OH have a synergistic effect that is greater than the sum of the individual differences.…”
Section: Resultsmentioning
confidence: 93%
“…Previously, we showed that absence of the 4-OH alone had a relatively small influence on antigenic potency and a Ͻ5-fold effect on equilibrium binding of a soluble TCR or binding of CD1d tetramers loaded with this variant glycolipid to live cells (28). The shorter C 8 acyl chain of PBS-25 and a C 14 analog of ␣-GalCer also did not cause a great decrease in antigenic potency (29,30). Based on these findings, we conclude that the combined differences of the shortened acyl chain and the absence of the sphingosine 4-OH have a synergistic effect that is greater than the sum of the individual differences.…”
Section: Resultsmentioning
confidence: 93%
“…30 In consideration of the intrinsic instability of O-glycosides in vivo, both C-bridged glycoside (α-C-GalCer) 31−33 and S-bridged glycoside (α-S-GalCer), 34−36 with the replacement of the anomeric oxygen by methylene or sulfur atom, respectively, were prepared to examine their biological activities. Comparing to the O-glycoside KRN7000, α-C-GalCer showed a stronger Th1 response in vivo, whereas the analogue α-S-GalCer did not activate the murine iNKT cells both in vitro and in vivo, but stimulated human iNKT cells in vitro.…”
Section: −27mentioning
confidence: 99%
“…23−27 For example, KRN7000 analogue with a longer acyl tail (2, Figure 1) exhibited a greater ability for activation of B cells and induced IL-2 from mouse NKT cells, and IL-4 and IFN-γ from human Vα24i NKT cells in vitro, 28,29 while the analogue with a relative shorter chain (3, Figure 1) influenced cytokine release toward Th2 bias with an immunomodulatory response. 30 In consideration of the intrinsic instability of O-glycosides in vivo, both C-bridged glycoside (α-C-GalCer) 31−33 and S-bridged glycoside (α-S-GalCer), 34−36 with the replacement of the anomeric oxygen by methylene or sulfur atom, respectively, were prepared to examine their biological activities. Comparing to the O-glycoside KRN7000, α-C-GalCer showed a stronger Th1 response in vivo, whereas the analogue α-S-GalCer did not activate the murine iNKT cells both in vitro and in vivo, but stimulated human iNKT cells in vitro.…”
mentioning
confidence: 99%
“…Savage and coworkers showed that truncation of the fatty acyl or the phytosphingosine chains has shown to bias cytokine secretion toward a Th2 response. 45 Similarly, OCH selectively induces Th2 cytokines from NKT cells and suppressed autoimmune diseases such as experimental autoimmune encephalomyelitis (EAE) and diabetes in NOD mice. 46 Also, introduction of unsaturation into the fatty acyl chain of α-GalCer, C20:1 cis/trans and C20:2 analogs seem to bias toward a Th2 response.…”
Section: Modification Of Lipid Chainsmentioning
confidence: 99%